Heme oxygenase-1 (HO-1) protects human lens epithelial cells (SRA01/04) against hydrogen peroxide (H2O2)-induced oxidative stress and apoptosis. (May 2016) - Ma, Tianju; Chen, Tingjun; Li, Peng; Ye, Zi; Zhai, Wei; Jia, Liang; Chen, Wenqian; Sun, Ang; Huang, Yang; Wei, Shihui; Li, Zhaohui
Abstract: Objectives: This study aimed to investigate the protective role of heme oxygenase-1 (HO-1) in H2 O2 -induced oxidative stress and apoptosis in human lens epithelial cells (hLEC; SRA01/04). Methods: SRA01/04 cells were exposed to a hydrogen peroxide (H2 O2 ) concentration gradient and inducers of HO-1 such as cobalt protoporphyrin (CoPP) and zinc protoporphyrin (ZnPP), respectively. In addition, an RNA silencing experiment was conducted to investigate the HO-1 function in this study. A Cell Counting Kit-8 (CCK-8) assay was used to measure cell viability. Western blot and ELISA were used to detect the level of HO-1 expression. In our study, hLECs were exposed to 400 μM hydrogen peroxide (H2 O2 ) for 24 h with or without pretreatment with 10μΜ CoPP or 10μΜ ZnPP, respectively. Double immunofluorescence staining was used for cell identification and the qualitative expression of HO-1. Expression of HO-1 was monitored using Western blot and ELISA. Intracellular reactive oxygen species (ROS) were detected by flow cytometry analyses; commercial enzymatic kits were used to measure the levels of glutathione (GSH), as well as superoxide dismutase (SOD). The proportion of cell apoptosis was quantified by annexin V-fluorescein isothiocyanate (FITC)/propidium iodide (PI) staining. The expression of caspase family (−8, -3) proteins was measured by Western blot analysis. Results: HO-1 significantly restored the cell viability under H2 O2 injury via reducing the generation of ROS and increasing the levels of SOD and GSH activity. Moreover, HO-1 also inhibited H2 O2 -induced caspase-8 and caspase-3 proteins, thus significantly reducing the apoptosis of SRA01/04. An RNA silencing experiment demonstrated the increased resistance of LECs to oxidative stress specifically for increased levels of HO-1. Conclusions: These findings suggested that HO-1 protects human lens epithelial cells from H2 O2 -induced oxidant stress by upregulating antioxidant enzyme activity, reducing ROS generation, and thus inhibiting caspase family-dependent apoptosis. Highlights: Heme Oxygenase-1 (HO-1) is firstly investigated in Human Lens Epithelial Cells. HO-1 protects hLEC from H2 O2 –induced oxidant stress by up-regulating SOD and GSH. HO-1 reduces ROS generation and inhibit hLEC apoptosis. Zinc Protoporphyrin (ZnPP) acts as an inducer to HO-1.